Phase change heat transfer in a vertical metal foam-phase change material thermal energy storage heat dissipator - Ghalambaz, Mehdi; Mehryan, S.A.M.; Ramezani, Sayed Reza; Hajjar, Ahmad; El Kadri, Mohamad; Islam, Mohamamd S.; Younis, Obai; Ghodrat, Maryam (Journal of energy storage, 2023)
A metallic foam heat dissipator for cooling electronic components was addressed. A heat dissipator is a partitioned aluminum container loaded along with aluminum metallic foam and saturated with paraffin wax. A heat flux at a surface contains a basic uniform flux and the step transient raise, which should be managed by a heat dissipator and a Phase Change Material (PCM). The regulating equations for a melting/solidification transfer of heat & momentum transport in a heat dissipator were instituted into a structure of partial differential equations. Then, the vital monitoring equations were converted into a general dimensionless type and solved by the Finite Element Method. A mesh adjustment technique & automated time-step control was employed to control the accuracy & convergence of the result automatically. An adaptation technique controls the mesh resolution at the melting/solidification interface. The dimensionless temperature of fusion is a vital factor in the control of the surface temperature and heat dissipator efficiency. Considering a fixed amount of material for walls, a heat dissipator with thick sidewalls and thin top and bottom walls results in slightly better thermal performance. Using a PCM heat sink could reduce the heated surface temperature by >175 % during the pulse load. •The phase transition heat transfer was addressed in a vertical heat dissapiator with energy storage.•The heat dissapator is subject to a pulse heat flux and a cooling stream.•The heat dissapator could actively cool down the heated surface using the PCMs material.•Employing the phase change heat dissapiator could reduce the surface temperature by 175 %.•PCM's fusion temperature is a crucial parameter in the thermal behavior of the heat dissapator.